Relationship of Characters and Illustration in Short Story 9 Dari Nadira By Leila S. Chudori - Sri Ayu Kusumaningsih; Ahmad Bahtiar (ppjbsip, 2019)
This study is to find out the relationship of characters to illustrations in a collection of 9short stories from NadiraKarya Leila S. Chudori. In the collection, there are four short stories that contain illustrations of the main characters namely